Litiasis vesical por dispositivo intrauterino: presentación de un caso / Vesical lithiasis caused by Intra-uterine Device. A Case Report - Hernandez Campo, Pedro Ricardo; Castillo García, Verónica; Chala Castañeda, Yoel; Castillo García, Idelma; Llera Almirall, Pedro (Revista de Ciencias Médicas de Pinar del Río, 2012)
El uso del anticonceptivo, el dispositivo intrauterino (DIU) es aceptado muy bien por las mujeres, sin embargo, se han informado complicaciones tempranas y tardías incluyendo migración hacia otros órganos así como perforación del útero. Hasta el año 2004 solo existían reportados 36 casos en la literatura mundial; nosotros reportamos un caso que comenzó con disuria marcada después de colocado el dispositivo intrauterino y resultó que la formación de una litiasis intravesical de gran tamaño. Palabras clave: Vejiga, dispositivo intrauterino, litiasis vesical. ABSTRACT The use of the intra-uterine device (IUD) is well-accepted by women, though early and late complications are diagnosed including the migration to other organs and the perforation of the uterus. Until year 2004 only 36 cases were reported in the medical literature, a case suffering from a marked dysuria after using the device was reported and it resulted in the formation of a great intra-vesical lithiasis. Key words: Bladder, intra-uterine device, vesical lithiasis